(untitled) (International Journal of Multidisciplinary Perspectives in Higher Education, 2020)
In this essay, we describe how the cognitive apprenticeship model serves as a framework for mentoring early-career women faculty into the professoriate. We illuminate our ideas using the metaphor of a kaleidoscope to inspire and support women faculty as they grow as academic writers and build their academic identities.